Cross-cultural adaptation, reliability, and validity of a Chinese version of the pelvic girdle questionnaire - Hui Cong; Heng Liu; Yin Sun; Jinsong Gao; Juntao Liu; Liangkun Ma; Britt Stuge; Lixia Chen (BMC, 2021)
Abstract Background The Pelvic Girdle Questionnaire (PGQ) is the only specific instrument designed to evaluate pain and activity limitations in pregnant or postpartum women with pelvic girdle pain (PGP). This study aimed to translate and culturally adapt the PGQ for Chinese patients and to verify the validation of the psychometric items of the PGQ in the Chinese population. Methods First, the translation and cultural adaptation process of the PGQ was conducted on the basis of international guidelines. Eighteen women suffering from PGP (11 pregnant women and 7 postpartum women) were enrolled in the pilot tests. Second, a total of 130 pregnant and postpartum women with PGP were enrolled to evaluate the validation of the psychometric items of the Chinese version. Results The calculated Cronbach's alphas demonstrated a high level of internal consistency for the Chinese version of the PGQ, ranging from 0.77 to 0.93. The convergent validity showed a high positive correlation between the PGQ total score and the Oswestry Disability Index (0.84) and Numeric Rating Scale (0.73) for pain intensity. Furthermore, a good discriminatory ability was found for the Chinese version of the PGQ for distinguishing women who needed treatment from those not (area under the curve [AUC] = 0.843, p < 0.001), but not for discriminating the pregnant and postpartum states (AUC = 0.488, p = 0.824). The results of test-retest showed good reproducibility for the total PGQ (ICC = 0.93), the PGQ activity subscale (ICC = 0.92), and the PGQ symptom subscale (ICC = 0.77). Conclusion Our study presents the translation, validation and psychometric features of the Chinese version of the PGQ, showing good construct validity and discriminative power for assessing the consequences of PGP among pregnant or postpartum Chinese women.